Play Therapy as a Method of Fine Motor Stimulation for Hospitalized Children with Acute Lymphoblastic Leukemia - Azahra Chairani Hamed; Hana Rizmadewi Agustina; Hartiah Haroen (Multidisciplinary Journals, 2026)
Children with Acute Lymphoblastic Leukaemia (LLA) are at risk of developmental delays due to the effects of long-term therapy and repeated hospitalisations. This study aims to describe the application of fine motor development stimulation through play therapy, based on the family-centred care approach, for children with LLA who experience developmental delays. Methods: This study used a case study design on a 2-year-old hospitalized at RSUD Welas Asih. Denver II results indicated a delay in fine motor development because he was unable to grasp a pencil or scribble on paper. The intervention lasted 4 days and included family education, pencil-grasping exercises, scribbling activities, and the introduction of simple puzzles. The result showed an improvement in fine motor coordination, with a score increase from 7 to 8. Active family involvement during therapy enhanced the child’s motivation and supported the continuity of stimulation at home. This simple intervention proved effective in supporting the fine motor development of children with chronic diseases and aligned with principles of pediatric palliative care, which focus on improving the quality of life of children and families. Ongoing stimulation and continued use of puzzle activities at home are recommended to further strengthen hand coordination and concentration skills.